2020
DOI: 10.1016/j.cegh.2020.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ willingness to be vaccinated with a smallpox vaccine to prevent monkeypox viral infection: A cross-sectional study in Indonesia

Abstract: Background: Although there is no licensed vaccine for monkeypox, smallpox vaccine has been shown to be 85% effective in preventing the monkeypox. This study was conducted to assess the willingness of frontline healthcare providers to be vaccinated with smallpox vaccine to prevent monkeypox. Methods: A cross-sectional study was conducted in Indonesia. The willingness was assessed under two scenarios: fully subsidized and non-subsidized vaccine. Explanatory variables such as sociodemographic profile, workplace a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 26 publications
2
25
1
Order By: Relevance
“…This results make sense knowing that healthcare workers are in the frontline in ghting any health threat and thus the risk of their contamination and thus they are prioritized in any vaccination strategy as it was the case of COVID-19. These results are in accordance with the results of previous studies conducted in Indonesia before the COVID-19 pandemic where the rate of acceptance could reach 96% [33,34] The second important results is the high rate of hesitancy among the general population especially in Romania were only 29% had a favorable attitude towards vaccination [26]. These low rates of acceptance/willingness go in the same direction with the rates obtained for COVID-19 vaccines especially in the rst months of their approvals.…”
Section: Discussionsupporting
confidence: 90%
“…This results make sense knowing that healthcare workers are in the frontline in ghting any health threat and thus the risk of their contamination and thus they are prioritized in any vaccination strategy as it was the case of COVID-19. These results are in accordance with the results of previous studies conducted in Indonesia before the COVID-19 pandemic where the rate of acceptance could reach 96% [33,34] The second important results is the high rate of hesitancy among the general population especially in Romania were only 29% had a favorable attitude towards vaccination [26]. These low rates of acceptance/willingness go in the same direction with the rates obtained for COVID-19 vaccines especially in the rst months of their approvals.…”
Section: Discussionsupporting
confidence: 90%
“…According to UNESCO Indonesia, the literacy rate of adults (aged 15 and above) was 95.98% (42) and previous studies using community samples found that at least 96% of the community graduated from primary school (26,43). As reported in other online studies in Indonesia (44)(45)(46)(47), selection bias could also be related to the sampling technique and differential access to internet infrastructure across the country, as some regions have better internet access than others. Finally, acceptance was assessed using a hypothetical vaccine, which may differ from the respondents' revealed preferences in a reallife situation.…”
Section: Discussionmentioning
confidence: 93%
“…However, the attitude toward vaccination was positive, despite concerns expressed by the WHO in 2019 about vaccine hesitation, which was ranked among the 10 threats to global health. In Indonesia, even before the COVID-19 pandemic, over 90% of doctors participating in a cross-sectional study about the attitude toward monkeypox vaccination were willing to be vaccinated [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…One asymptomatic HCW showed laboratory evidence of recent Orthopoxvirus infection, which was possibly attributable to either a recent infection or smallpox vaccination. Harapan 2020a [ 32 ] Indonesia Cross-sectional study Knowledge and attitudes of physicians toward monkeypox virus Among 407 Indonesian doctors, 96% expressed acceptance of a free vaccination. Those 30 years old or younger had 2.94 times greater odds of vaccine acceptance compared to those who were older.…”
Section: Table A1mentioning
confidence: 99%